Comparative Study of Signalized Intersection Performance Analysis Methods - Bobby Agung Hermawan; I Made Arka Hermawan; Anasta Wirawan; Edi Santosa; Veronica; Alfath Satria Negara Syaban; Setya Wijayanta (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2025)
At intersections, traffic performance indicators consist of saturation degree, queue length, and delay. There are several methods commonly used to calculate performance indicators at intersections, including the PKJI method (2023) and the RJ method. Salter (1981). Each method produces different performance values. Between the PKJI 2023 method and the RJ method, it is not yet known which method is most representative of field conditions, therefore it is necessary to identify which method produces performance that is most in accordance with real conditions in the field. There are several differences and similarities between the analysis of signalized intersections with the PKJI 2023 and RJ methods. Salter, namely the emp value between the PKJI 2023 method and the RJ Salter method, it can be seen that the PKJI 2023 method divides the emp into 2 (two), namely protected and opposed emp, while RJ Salter does not divide it. The magnitude of the emp value is also different for each type of vehicle, this is likely due to the characteristics of vehicle behavior and the geometry of the intersection. In addition, the saturation current formula between the two methods is different, but in the PKJI 2023 and RJ methods. Salter has a So variable (basic saturation current) in the formula. Calculation of cycle time analysis, green time, and approach capacity of the 2nd intersection method with the same approach. Calculation of traffic behavior in this case the queue length and traffic delay from the 2 methods are different. The results of the Mann-Whitney test between the median performance parameters from the survey results and PKJI 2023 show that there is a difference. While the test results between PKJI 2023 and RJ. Salter there is no difference.